The neXt Dirac incarnation - Stagni,F; Boyer,A; Tsaregorodtsev,A; Haen,C; Burr,C; Bauer,D; Fayer,S; Martyniak,J (2025)
The DIRAC interware has long served as a vital resource for user communities seeking access to distributed computing resources. Originating within the LHCb collaboration around 2000, DIRAC has undergone significant evolution. Despite its efficacy in meeting experiment-specific requirements, DIRAC has accrued technical debt over its 15-year history. Installation management remains intricate, with significant entry barriers and a reliance on bespoke infrastructure. The software development process lacks alignment with contemporary standards, impeding the onboarding process for new developers. Notably, integral components such as the network protocol and authentication mechanisms are proprietary and pose challenges for seamless integration with external applications. In response to these challenges, the DIRAC consortium has embarked on the development of DiracX. DiracX heralds a new era in distributed computing solutions. This contribution describes technical decisions, roadmap and timelines for the development of DiracX, while recognizing the criticality of maintaining a continuously operational DIRAC system for numerous user communities.